The Effects of Increasing Running Speed on the Displacement and Velocity of the Center of Pressure - Mohadeseh Jafari Rajeouni; Razieh Yousefian Molla; Ali Fatahi (Islamic Azad University, Hamedan Branch, 2023)
Objective The aim of this study was to determine the effect of increasing running speed on the displacement and speed of the center of sole pressure. Methods For this purpose, 28 professional runners with at least 5 years of experience in athletics, from among Tehran province teams in the national league, were selected as volunteers as a sample. After completing the informed consent form, the subjects first walked at a speed of 1.2 meters per hour to get acquainted with the treadmill. Then, slowly, the speed reached 2.5 meters per second, and after 3 minutes of running at this speed, the data were recorded for about thirty seconds. The runners then ran on the treadmill at a speed of 3.5 m / s and then at a speed of 4.5 m / s. Data were collected using special markers and 3D cameras. Analysis of variance with repeated measures and Bonferroni post hoc test were also used to analyze the data. Results The results showed that increasing the running speed would have a significant effect on the displacement rate and foot pressure of runners. As the running speed increased, so did the displacement and the pressure of the sole of the foot. Conclusion The results confirm the effect of increasing running speed on the amount of movement and speed of foot pressure.